Validation of the Arabic Version of Medication Regimen Complexity Index Among Older Patients - Validation of the “MRCI-Arabic” - Nilay Aksoy; Nur Ozturk; Betul Okuyan; Mesut Sancar (Sudan Journal of Medical Sciences)
The medication regimen complexity index is widely used in clinical practice and many studies, to assess the complexity of medication regimens. The goal of this study is to validate the medication regimen complexity index-Arabic (MRCI-Arabic) version among older patients. Methods: This methodologic study was conducted in older patients (≥ 65 years old) who were native Arabic speakers at a community pharmacy located in Istanbul, Turkey. After the translation and cultural adaptation process finished, medication regimens of 30 patients were evaluated for test-retest reliability three weeks apart by the rater who was a native Arabic speaker. The inter-rater correlation was calculated in study population (n =100). The link between the number of medications and the score of medication regimen complexity was used to assess convergent validity. The difference in the score of pharmaceutical regimen complexity in stratified age groups was used to examine discriminant validity. Results: The inter-rater and test-retest reliability of the MRCI-Arabic total scale and its subsection were extremely high (Spearman’s rho ranged from 0.996 to 1; p <0.001). There was a strong and positive correlation between the total MRCI-Arabic score and the number of medications (r = 0.830; p < 0.001), the number of chronic diseases (r = 0.641; p < 0.001). Conclusion: The Arabic validation of the MRCI is a validated tool that can be used by native Arabic-speaking healthcare professionals to determine the complexity of their patients’ medication regimens.